Asymmetrical multilevel inverter topology with reduced number of switches - Ahmed, R.A.; Mekhilef, Saad; Ping, H.W. (Praise Worthy Prize, 2012)
A new asymmetrical multilevel inverter topology with reduced number of power switches is introduced in this paper. The installation area, voltage standing on each switch, converter cost and losses are also taken into consideration in this design. Further, operating principles and switching functions are analyzed. A comparative study between the new design and conventional inverters is also conducted to highlight the advantages of the proposed topology. Simulation results are provided for seven level of the asymmetrical multilevel inverter. A prototype of the designed inverter is manufactured and experimental results are realized.